Molecular Characterization of Malaysian Isolates of Newcastle Disease Viruses and the Development of a Duplex RT-PCR for Simultaneous Diagnosis of Newcastle Disease and Avian Influenza - Mekonnen, Ayalew Berhanu (2010)
Newcastle disease (ND) sporadic cases have been occasionally occurred in Malaysia and remain a constant threat to poultry industry despite routine vaccination programs. Hence in the present study, eleven ND virus isolates obtained from clinical cases between 2004 and 2007 were characterized based on sequence and phylogenetic analysis. The coding region of F gene and carboxyl terminal region including extensions were amplified by reverse transcriptase polymerase chain reaction (RT-PCR) and directly sequenced. All isolates have shown to have non-synonymous to synonymous base substitution rate ranging between 0.081 – 0.264 demonstrating presence of negative Generally, the current isolates possess three different of cleavage site motifs; namely 112RRQKRF117, 112RRRKRF117 and 112GRQGRL117. On further characterization, current Malaysian isolates had HN extensions of 0, 6 or 11 amino acids. Analysis of the phylogenetic tree revealed that the Malaysian isolates belong to three genetic groups: II, VII and VIII in which majority of the isolates were classified in genotype VII. A duplex RT-PCR assay was developed and evaluated for the specific discrimination of NDV and avian influenza viruses (AIV) by using NP gene specific primers. PCR products of expected size 243bp and 170bp fragment of NDV and AIV, respectively, were amplified from NDV and AIV isolates while none of the viral genomes from other avian viruses and other heterologous avian pathogens gave a visible band of the expected size indicating that primers are highly specific. The developed assay had a sensitivity limit up to 150pg per reaction of total RNA and 4 x10 -1 HAU. A study of 65 each NDV and AIV clinical trial samples, proved the applicability of this method in detecting viral nucleic acids from various tissue and swab samples. The specific evaluation of the performance of dRT-PCR indicated that the assay seemed to be less sensitive for NDV detection but more sensitive for AIV detection than standard virus isolation methods. However, out dRT-PCR offers the advantage of being easier to perform (one step) and much faster by saving considerable time and effort needed for individual test than conventional methods. In conclusion, we developed a robust, rapid and specific dRT-PCR assay for detection and differentiation of ND and AI viruses in clinical and field samples and should be further improved especially in the development of an internal control. The wide spread occurrence of a variety of NDV genotypes and presence of varied carboxyl terminus extension lengths demonstrated the existence of genetic diversity within Malaysian isolates.